2012
DOI: 10.1097/sle.0b013e3182478e6c
|View full text |Cite
|
Sign up to set email alerts
|

Are Short-term Focused Training Courses on a Phantom Model Using Porcine Gall Bladder Useful for Trainees in Acquiring Basic Laparoscopic Skills?

Abstract: The best training method in laparoscopic surgery has not been defined. We evaluated the efficacy of laparoscopic skills acquisition in a short-term focused program. Two hundred fifty-six participants undergoing training on a phantom model were divided into 2 groups. Group 1 had no exposure and group 2 had performed a few laparoscopic surgeries. Acquisition of laparoscopic skills was assessed by operation time and the modified Global Operative Assessment of Laparoscopic Skills (GOALS) scale. A questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…911 Each course consisted of 6 participants, and participants from both the groups were randomly allotted to a course. The course consisted of a video demonstration on principles of laparoscopic suturing that was followed by 2 h of practicing laparoscopic suturing on a cloth model with the help of instructors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…911 Each course consisted of 6 participants, and participants from both the groups were randomly allotted to a course. The course consisted of a video demonstration on principles of laparoscopic suturing that was followed by 2 h of practicing laparoscopic suturing on a cloth model with the help of instructors.…”
Section: Methodsmentioning
confidence: 99%
“…911 The trainees in both the groups were given no verbal or physical help to complete the anastomosis. The performance in the first case was taken as the baseline performance, and performance in the fifth case was taken as the final score.…”
Section: Methodsmentioning
confidence: 99%
“…They can obtain the training effect of surgical procedures in a short time. Our previous studies have shown that this trainer is effective in imparting training to novice surgeons by providing a real-time simulation of the OR 3,4,6. In a previous study done on this module, we have shown that the trainees acquire the laparoscopic skills effectively and showed statistically significant improvement in all domains of GOALS by the end of their training 4.…”
Section: Discussionmentioning
confidence: 82%
“…On the contrary, there is substantial literature that supports the use of short-course format for medical and surgical primary education as well as continuing medical education (Morino et al, 1995;Keleher et al, 2005;Cheifetz and Phang, 2006;Patel et al, 2008;Scott et al, 2008;Devine et al, 2009;Bansal et al, 2012;Wilkins et al, 2015). There is objective and subjective knowledge retention and maintenance of skills at follow-up dates as long as 17 months (Keleher et al, 2005;Cheifetz and Phang, 2006;Scott et al, 2008;Devine et al, 2009;Bansal et al, 2012;Wilkins et al, 2015). There is evidence that maintenance of surgical skills requires continuing use of those skills garnered (Patel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…From a broader perspective, short-course style learning experiences are becoming more common in medical and surgical education given demands on time, resources, and the complicated ethics of health-care education (Patel et al, 2008;Bansal et al, 2012). The effectiveness and maintenance of knowledge and skills garnered from a short-course format learning experience has been challenged in the literature (Mackay, 2006;Malling et al, 2009).…”
Section: Discussionmentioning
confidence: 99%